2016
DOI: 10.2147/tcrm.s98165
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems in a sample of outpatients with chronic diseases: a cross-sectional study from Jordan

Abstract: Optimization of drug therapy and preventing drug-related problems (DRPs) are major factors to improve health care, reduce expenditure, and potentially save lives. This study aimed at describing the types, numbers, and frequencies of DRPs in the outpatient settings of a group of hospitals in Jordan. The study was set in the cardiology, endocrine, and respiratory outpatient clinics of five major hospitals in Jordan. Patients who visited the above clinics during the period from September 2012 to December 2013, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 25 publications
7
53
2
5
Order By: Relevance
“…In our study, bisoprolol was the most problematic Bold values are at high level than the others drug in relation to dose selection (Appendix 1). The inappropriate dosing of the study accounted for the lower result when comparing to previous study [20], with 42.5%. Too low doses may reduce the therapeutic effect; too high doses are also a serious problem in healthcare.…”
Section: Discussionmentioning
confidence: 65%
“…In our study, bisoprolol was the most problematic Bold values are at high level than the others drug in relation to dose selection (Appendix 1). The inappropriate dosing of the study accounted for the lower result when comparing to previous study [20], with 42.5%. Too low doses may reduce the therapeutic effect; too high doses are also a serious problem in healthcare.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, various studies have demonstrated its effectiveness on clinical (14,15,(17)(18)(19)(20)(21)(22)(23)(24), economic (17,22,23,25) and humanistic outcomes (26,27). Other studies determined some factors associated with the occurrence of DTPs, such as polypharmacy, multimorbidity and age, yet employed methodology or clinical settings dissimilar to the present study (28)(29)(30)(31). However, to the best of authors' knowledge, until now, no study determined the associated factors of patients with chronic diseases at the primary care level as they receive CMM services that follow the theoretical framework proposed by Cipolle et al (9).…”
mentioning
confidence: 93%
“…That has included a visit the doctor at ambulatory care clinic or emergency visit, hospital admission, or critical care admission or death. [3][4][5][6][7][8][9][10][11] Most of the studies done retrospective or perspective with follow up. There's not involved the patient respective and view.…”
Section: Introductionmentioning
confidence: 99%